A novel income security intervention to address poverty in a primary care setting: a retrospective chart review. Issue 8 (17th August 2017) - Jones, Marcella K; Bloch, Gary; Pinto, Andrew D
Abstract : Objective: To examine the development and implementation of a novel income security intervention in primary care. Design: A retrospective, descriptive chart review of all patients referred to the Income Security Heath Promotion service during the first year of the service (December 2013–December 2014). Setting: A multisite interdisciplinary primary care organisation in inner city Toronto, Canada, serving over 40 000 patients. Participants: The study population included 181 patients (53% female, mean age 48 years) who were referred to the Income Security Health Promotion service and engaged in care. Intervention: The Income Security Health Promotion service consists of a trained health promoter who provides a mixture of expert advice and case management to patients to improve income security. An advisory group, made up of physicians, social workers, a community engagement specialist and a clinical manager, supports the service. Outcome measures: Sociodemographic information, health status, referral information and encounter details were collected from patient charts. Results: Encounters focused on helping patients with increasing their income (77.4%), reducing their expenses (58.6%) and improving their financial literacy (26.5%). The health promoter provided an array of services to patients, including assistance with taxes, connecting to community services, budgeting and accessing free services. The service could be improved with more specific goal setting, better links to other members of the healthcare team and implementing routine follow-up with each patient after discharge. Conclusions: Income Security Health Promotion is a novel service within primary care to assist vulnerable patients with a key social determinant of health. This study is a preliminary look at understanding the functioning of the service. Future research will examine the impact of the Income Security Health Promotion service on income security, financial literacy, engagement with health services and health outcomes.